1995
DOI: 10.1210/jcem.80.3.7883823
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurements of bone density and biochemical indices in untreated primary hyperparathyroidism.

Abstract: A large number of patients with primary hyperparathyroidism today do not undergo parathyroidectomy. In this prospective study, we evaluated the effect of untreated disease on biochemical and bone densitometric indices. In 66 patients, seven annual measurements showed no change in serum calcium, phosphorus, PTH, vitamin D, or alkaline phosphatase; in urinary calcium, hydroxyproline or hydroxypyridinium cross-link excretion; or lumbar spine, femoral neck, and radial bone mineral density. The subset of postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
3
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 15 publications
6
30
3
3
Order By: Relevance
“…Similar results were obtained by previous studies (Silverberg et al, 1995aAbdelhadi & Nordenstrom, 1998). Similar results were obtained by previous studies (Silverberg et al, 1995aAbdelhadi & Nordenstrom, 1998).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained by previous studies (Silverberg et al, 1995aAbdelhadi & Nordenstrom, 1998). Similar results were obtained by previous studies (Silverberg et al, 1995aAbdelhadi & Nordenstrom, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…A similar effect of PTX on BMD in pHPT patients was found in a long-term study (Martin et al ., 1990;Silverberg et al ., 1995b). Most pHPT patients without PTX have been reported to be clinically stable over the long-term (Silverberg et al ., 1995a;Abdelhadi & Nordenstrom, 1998). (1999) subsequently reported that successful surgery led to sustained increases in BMD at trabecular but not cortical sites during 10 years of follow-up after PTX and that cortical bone loss was irreversible at the time of diagnosis.…”
mentioning
confidence: 99%
“…[2][3][4][5] Compared with s-HPT, HPT/MEN1 presents as a multiglandular parathyroid neoplasia (hyperplasia vs. adenoma); has an earlier disease onset (20 vs. 40 years of age); is frequently less aggressive; harbours a germline mutation in the MEN1 gene that is not found in s-HPT; has a higher recurrence rate after a parathyroidectomy (PTx) and the recommended surgical approach in HPT/MEN1 is subtotal or total PTx, whereas adenomectomy is indicated for s-HPT. 7,11,12 BMD values in the LS are either slightly diminished or even normal in s-HPT, [11][12][13] which clearly contrasts with the vertebral demineralization so far reported in HPT/MEN1. Excess of PTH in HPT increases bone turnover, leading to a reversible loss of cortical and trabecular bone caused by an expansion of the remodelling space, and an irreversible loss of cortical bone caused by increased endocortical resorption.…”
Section: Introductioncontrasting
confidence: 71%
“…The work of Silverberg and her colleagues have demonstrated that in the mild asymptomatic form of the disease seen today, a particular pattern occurs in terms of bone density (49). The work of Silverberg and her colleagues have demonstrated that in the mild asymptomatic form of the disease seen today, a particular pattern occurs in terms of bone density (49).…”
Section: Mechanism Of Pth Action On Bonementioning
confidence: 99%